Psicoterapia para crianças e adolescentes abrigados: construindo uma forma de atuação - Marmelsztejn, Renata (2006)
This study is about some challenges psychotherapists have to face when attending institutionalized children and adolescents. It is a qualitative analysis of interviews with eight psychotherapists that attended more then one client for a period of at least one year. The meanings brought by those subjects made possible to precise some common characteristics: they were all strongly committed to social projects and intended to make personal contributions and they also presented tolerance, persistence, stability, availability, flexibility and creativity. One important challenge was how to deal with the sociometric network surrounding those clients like the shelters conflicts and their dysfunctional family of origin. Issues like violence, abandonment, lost of related ones, the complexity of the legislation related to institutions were discussed. One paradox was that the shelter could represent a safe-continent place, or again perpetrate violence and abandonment. The psychotherapist had to deal with a pool of different questions like: to identify the demands of the clients, to construct bonds with the young, to integrate the different realities of the client and the therapist, to deal with their own feelings during the treatment, to construct a partnership relation with the institution and finally to understand the function of psychotherapy with sheltered clients. The author concludes that psychotherapy in those conditions could be actually a helpful way to elaborate the experience of violence and abandonment. She also pointed out some important directions for the selection and training of professionals in this area